Graphene loaded TiO2 submicron spheres scattering layer for efficient dye-sensitized solar cell. (April 2023) - Shahid, Muhammad Umair; Mohamed, Norani Muti; Muhsan, Ali Samer; Azella Zaine, Siti Nur; Khatani, Mehboob; Yar, Asfand; Ahmad, Waqar; Hussain, Muhammad Babar; Alothman, Asma A.; Saleh Mushab, Mohammed Sheikh
Abstract: Dye-Sensitized Solar Cells (DSSCs) have attracted great attention due to environmentally friendly low-cost processing, excellent working ability in diffuse light, and potential to meet the power demands of future buildings due the true class of building integrated photovoltaics (BIPV). Nevertheless, DSSCs have relatively low photoconversion efficiency (PCE) due to multiple issues. Several strategies have been employed to enhance its PCE. For instance, bi-layered structure of photoelectrode i.e., mesoporous TiO2 transparent layer with top scattering layer was introduced which scatter light inside on large angles improves the harvesting ability of photoelectrode thus enhanced PCE. However, scattering layer is composed of aggregated small particles which offer sluggish electron transport due to multiple grain boundaries, consequently, unwanted recombination reaction which leads to poor PCE. This issue has been addressed for transparent layer immensely but ignored for scattering layer. Mostly for scattering layer in previous studies novel structures have been proposed to enhance scattering properties and dye adsorption only. Therefore, in this study for the first time presenting dual functional graphene/TiO2 scattering layer in which solvent exfoliated graphene is incorporated in TiO2 submicron spheres which enhanced electron transport properties, while submicron spheres scatter light effectively. Scattering and electron transport characteristics of DSSCs are thoroughly investigated with the function of graphene loading. Electrochemical impedance spectroscopy (EIS) has revealed that diffusion coefficient length and coefficient and conductivity attained maximum value at 0.01 wt%. while other important parameters such as electron lifetime and electron density in conduction band have been improved till 0.020 wt% graphene loading. However, results indicated that with 0.01 w% graphene 33% higher PCE was achieved than without scattering layer and 13% higher than scattering layer without graphene. The depraving in PCE at >0.01 wt% graphene despite of excellent electron transport improvement is attributed to the loss of diffuse reflectance and higher optical absorption by graphene. Graphical abstract: Image 1 Highlights: Dual functional graphene/TiO2 scattering layer presented to improve PCE. Graphene drastically improved electron lifetime and diffusion length. At optimum graphene loading, 33% higher PCE is achieved than without scattering layer. Graphene incorporation does not support to improve scattering properties.